Transnational Education and Its Place in the Uzbekistan Education System - Rakhimov Oktyabr Dustkabilovich; Azizov Shavkat Abdurakhmanovich (Lembaga Yasin AlSys, 2026)
Transnational education has become an important mechanism for expanding access to internationally oriented higher education and strengthening the quality and competitiveness of national education systems. This article aims to elucidate the essence, goals, and objectives of transnational education, examine the conditions required for implementing transnational education programs, and analyze issues related to quality assurance and development within the framework of transnational education. The article also substantiates the legal foundations for the development of transnational education in Uzbekistan, analyzes the achievements and shortcomings observed to date, and outlines the main directions for its further advancement. The discussion highlights that effective implementation of transnational education requires clear regulatory support, quality assurance mechanisms, alignment with educational standards, and cooperation between provider universities and local institutions. The article concludes that strengthening the legal, institutional, and accreditation frameworks for transnational education is essential for improving program quality, ensuring accountability, and supporting the sustainable development of higher education in Uzbekistan. This study contributes to the literature on internationalization and higher education policy by clarifying the conceptual, legal, and quality assurance dimensions of transnational education in the Uzbek context.